Choice of location, growth and welfare with unequal pollution exposures - Lich, Hoang Khac; Tournemaine, Frédéric (Technological and Economic Development of Economy, 2014)
We develop an endogenous growth model with human capital accumulation in which firms are polluting and heterogeneous individuals must decide, among other things, where to live. The main idea is that pollution is unequally spread across geographical locations, inducing a trade-off for individuals between environmental quality and leisure. In such economy, we show that a better environmental quality and/or a greater degree of inequality lead individuals to favour cleaner locations which, in turn, boosts long-term growth. Welfare-wise, we find that, in general, individuals prefer a greater level of consumption and leisure but lower growth and environmental quality than those which are possible to achieve. Moreover, we show that the sign of the impact of inequality on environmental quality is likely to be negative.